National Broadcasting and State Policy in Arab Countries - Guaaybess, T.; Guaaybess, T. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2013)
A state-of-the-art analysis of the situation of national television in Arab countries, addressing what Arab national broadcastings today say about public policy and political opening. The essays deal with the reforms of public broadcasting organizations and the evolution, perspectives and issues of national broadcasting.